IOT Based Automatic Plant Watering and Tank Filling System - Das, Sattik; Pandit, Nivedita; Gupta, Nandita; Ray, Anjali; chatterjee, Sumanta; Paul, Apurba (International Journal of Computer Sciences and Engineering, 2025)
The Internet of Things (IOT) defines that objects are interconnected through wired and wireless networks without user intervention. The current IOT perform, sensing, actuating, data gathering, storing, and processing by connecting physical or virtual devices to the Internet. In this paper a model of automated plant watering system has proposed. It is a model of controlling watering system to the plants. Automatic plant watering system is a technological solution that enables automating the bulk of electronic, electrical and technology based task within a home or in the garden. It uses a combination of hardware and software technology that enables control and management of water supply to the plants automatically.